Tree-Inspired Structurally Graded Aerogel with Synergistic Water, Salt, and Thermal Transport for High-Salinity Solar-Powered Evaporation - Zhao, Xiaomeng; Zhang, Heng; Chan, Kit‑Ying; Huang, Xinyue; Yang, Yunfei; Shen, Xi (Nano-Micro Letters, 2024)
Solar-powered interfacial evaporation is an energy-efficient solution for water scarcity. It requires solar absorbers to facilitate upward water transport and limit the heat to the surface for efficient evaporation. Furthermore, downward salt ion transport is also desired to prevent salt accumulation. However, achieving simultaneously fast water uptake, downward salt transport, and heat localization is challenging due to highly coupled water, mass, and thermal transport. Here, we develop a structurally graded aerogel inspired by tree transport systems to collectively optimize water, salt, and thermal transport. The arched aerogel features root-like, fan-shaped microchannels for rapid water uptake and downward salt diffusion, and horizontally aligned pores near the surface for heat localization through maximizing solar absorption and minimizing conductive heat loss. These structural characteristics gave rise to consistent evaporation rates of 2.09 kg m−2 h−1 under one-sun illumination in a 3.5 wt% NaCl solution for 7 days without degradation. Even in a high-salinity solution of 20 wt% NaCl, the evaporation rates maintained stable at 1.94 kg m−2 h−1 for 8 h without salt crystal formation. This work offers a novel microstructural design to address the complex interplay of water, salt, and thermal transport. Highlights: 1 Inspired by transport system in trees, a two-way water and salt transport mechanism is realized in a structurally graded aerogel, enabling simultaneous fast water uptake and salt rejection. 2 The horizontally aligned pore channels near the surface achieve excellent heat localization by maximizing solar absorption and minimizing heat loss. 3 The integrated water, salt, and thermal transports impart an impressive evaporation rate of 1.94 kg m−2 h−1 in a 20 wt% NaCl solution for 8 h without salt accumulation.